3D kinematics applied to the study of individual BMX gate start technique - Gianikellis, K.; Skiadopoulos, A.; Bote, A. (ISBS - Conference Proceedings Archive (Konstanz), 2011)
Even if the BMX modality has been included in the schedule of the Olympic Games since Beijing 2008, there is a lack of scientific studies concerning this sport. According to the opinion of many trainers and experts, the start of the race is very important and both neuromuscular potential and sport technique are very relevant aspects of sport performance. The purpose of this study was to analyze the technique of three top young athletes of BMX during the starting gate in order to obtain relevant information to support their trainer's decisions.